PECULIARITIES OF OPTIMIZATION OF THE STRUCTURE OF CULTIVATED AREAS OF AGRICULTURAL CROPS IN THE CONDITIONS OF TRANSFORMATION OF LAND RELATIONS - Tykhenko , Ruslan (Collection of scientific papers «ΛΌГOΣ», 2022)
Modern global trends in the development of agricultural land use convincingly prove the need to solve, along with the task of providing the population with food, the problems of environmental protection, preservation of biodiversity, reproduction of soil fertility [4, 10, 24]. That is why such systems of land use are formed, which prioritize not the maximum productivity of crops, but the preservation of functional connections between natural elements of the environment. Adaptive landscape systems of land use fully correspond to such directions, the main principles of which are environmental friendliness, adaptability, scientific capacity and biogenicity [2, 6, 11, 30].